Pengurangan Ketidakpastian Desk Collection dalam Penagihan Tunggakan Nasabah PayLater - Widodo, Dimas Agung; Nurbayti, Nurbayti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
A desk collection agent in an e-commerce platform faces significant challenges in collecting PayLater installments from delinquent customers. This study aims to analyze how professional pressures and communication strategies in desk collection are employed to reduce uncertainty when dealing with PayLater customers who frequently evade their responsibilities. The study utilizes Uncertainty Reduction Theory to examine the psychological pressures and communication strategies used to alleviate uncertainty arising from customer reactions. A qualitative phenomenological approach is applied to collect data on PayLater arrears from the perspective of desk collection agents through in-depth interviews with six informants from three e-commerce platforms. The findings indicate that difficulties in contacting delinquent customers, despite adherence to company regulations and OJK (Financial Services Authority) guidelines, contribute to stress and anxiety due to the potential failure to meet daily targets. However, when desk collection agents employ non-procedural strategies, such as tracking through social media, Google Maps, and posing as field collectors, the success rate increases. Another challenge identified is the interaction with uncooperative customers, which often leads to the use of intimidatory strategies.